5-Androstenediol Ameliorates Pleurisy, Septic Shock, and Experimental Autoimmune Encephalomyelitis in Mice. (18th May 2010) - Nicoletti, Ferdinando; Auci, Dominick L.; Mangano, Katia; Flores-Riveros, Jaime; Villegas, Sonia; Frincke, James M.; Reading, Christopher L.; Offner, Halina
Abstract : Androstenediol (androst-5-ene-3β, 17β -diol; 5-AED), a natural adrenal steroid, has been shown to suppress experimental autoimmune encephalomyelitis (EAE) in female SJL/J mice. We here report that 5-AED limits inflammation and proinflammatory cytokines including TNFα in murine models of carrageenan-induced pleurisy and lippopolysaccaride- (LPS) induced septic shock. 5-AED binds to and transactivates sex steroid receptors with the same general rank order of potency (ER β > ER α ≫ AR). 5-AED provides benefit in EAE in a dose-dependent fashion, even when treatment is delayed until onset of disease. The minimally effective dose may be as low as 4 mg/kg in mice. However, benefit was not observed when 5-AED was given in soluble formulation, leading to a short half-life and rapid clearance. These observations suggest that treatment with 5-AED limits the production of pro-inflammatory cytokines in these animal models and, ultimately, when formulated and administered properly, may be beneficial for patients with multiple sclerosis and other Th1-driven autoimmune diseases.